Sunshine Correlated with Decreasing Death Outcome among Covid-19 Patients: Pre-Assuming Vitamin D that Triggered Immunity - Meita Veruswati; Al Asyary; Rony Darmawansyah Alnur; Aries Prasetyo (UHAMKA Press, 2020)
Previous decades, sunshine was taking as medication therapy for respiratory infectious as it triggered vitamin D in fostering body immune. The objective of this brief study is to estimate the outcome of Covid-19 patients as they were exposed by sunshine exposure in those were having care delivery in Surabaya referred hospitals, Indonesia. We collected and analyzed the available Covid-19 data from hospitals surveillance data from the local government of Surabaya data center, including the Meteorological, Climatological, and Geophysical Agency. Three outcomes of Covid-19 were investigated in this study includes: incidence, death, and recovered. The Covid-19 incidence in Surabaya was climbing over the period of investigation. Only the number of dead Covid-19 patients correlated significantly with sunshine exposure in those having care delivery in hospitals (p-value<0.01; r = -0.739). Our findings showed that sunshine correlated significantly with Covid-19’s death outcome in Surabaya.